2005
DOI: 10.3989/gya.2005.v56.i4.97
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of added natural antioxidants in sunflower oil

Abstract: RESUMENEfectividad de antioxidantes naturales adicionados a aceite de girasol..Se investigó la actividad antioxidante de ∝-tocoferol, δ-tocoferol, ácido cítrico y palmitato de ascorbilo en aceite de girasol con su conteniendo natural de tocoferol. La efectividad de los mismos fue analizada a través de la medida de la estabilidad oxidativa en Rancimat y el seguimiento de la oxidación con el almacenamiento a diferentes temperaturas. Las muestras extraídas periódicamen-te de la estufa fueron sometidas a los sigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…AP concentrations in the range of 100–850 ppm were found to be the most effective in reducing the rates of TBARS formation and loss of α‐TOH, which is comparable to effective AP levels reported in the literature . The synergistic effects of AP with primary antioxidants such as α‐TOH was suggested due to AP ability to partition in the water phase and reduction of tocopheroxy radicals and regeneration of tocopherols .…”
Section: Resultssupporting
confidence: 73%
“…AP concentrations in the range of 100–850 ppm were found to be the most effective in reducing the rates of TBARS formation and loss of α‐TOH, which is comparable to effective AP levels reported in the literature . The synergistic effects of AP with primary antioxidants such as α‐TOH was suggested due to AP ability to partition in the water phase and reduction of tocopheroxy radicals and regeneration of tocopherols .…”
Section: Resultssupporting
confidence: 73%
“…The same behavior was reported by Jimenez‐Patiño (), who reported shorter induction times for oils added with 630 ppm of extract of olive leaves than those exhibited when the extract was added at 250 ppm. The relationship between OSI and natural antioxidants concentration can be nonlinear (Carelli and others ) due to some antioxidants that are consumed in chain termination reactions during Rancimat assay, but also, in other side reactions, decreasing its efficacy at higher concentrations (Yanishlieva and Marinova, ), and consequently, causing a prooxidative effect in in vitro assays.…”
Section: Resultsmentioning
confidence: 99%
“…Since glycerol is a trihydroxy alcohol, monoacid, diacid and triacid esters are known. Carelli et al (2005) reported that the development of oxidative rancidity or autoxidation is the decisive factor affecting storage life and the use of edible oils and fats in food. Autoxidation of lipids is a natural process that occurs between molecular oxygen and unsaturated fatty acids through a freeradical chain mechanism that involves the formation of fat 'free radicals', peroxide 'free radicals' and hydro peroxides.…”
Section: Introductionmentioning
confidence: 99%